Rejuvenation; Influencing Factors That Farmers Should Consider - Siti Abir Wulandari; Zulkifili Alamsyah; Dompak Napitapulu; Ardi Novra (Randwick International of Social Science Journal, 2024)
One of the impacts of the replanting program is the cessation of production, which has implications for the loss of farmers' household sources of income. The production cycle in the business of annual crops greatly affects the profit that will be obtained by the farmer. More complicated challenges are faced by perennials than annuals because the time between investment, production, cost, and receipt of farming takes a long time in its implementation. This cross-sectional survey research aims to analyze the problems and socio-economic factors that determine the decision of oil palm farmers to participate in the rejuvenation of oil palm plantations in Jambi Province. This research was carried out in several villages which centered of smallholder oil palm plantations with a sample of 257 oil palm farmers who had old or damaged oil palm plants that had not been replanted or had been replanted. The respondents were selected by using the multistage sampling method. The instrument used is an open-ended questionnaire. The results showed that the farmer's level of readiness, assets, family size, dependency burden, sex ratio, and perception have a significant influence on the farmer's decision to replant oil palm. KEYWORDS Farmer; Palm oil; Rejuvenation; Sustainability